Management of broken dental implant abutment in a patient with bruxism: A rare case report and review of literature - Saad Al-Almaie (Wolters Kluwer Medknow Publications, 2017)
This rare case report describes prosthodontic complications resulting from a dental implant was placed surgically more distally in the area of the missing mandibular first molar with a cantilever effect and a crest width of >12 mm in a 59-year-old patient who had a history of bruxism. Fracture of abutment is a common complication in implant was placed in area with high occlusal forces. Inability to remove the broken abutment may most often end up in discarding the implant. Adding one more dental implant mesially to the previously placed implant, improvisation of technique to remove the broken abutment without sacrificing the osseointegrated dental implant, fabrication with cemented custom-made abutment to replace the broken abutment for the first implant, and the use of the two implants to replace a single molar restoration proved reliable and logical treatment solutions to avoid these prosthodontic complications.